Impact of the COVID-19 pandemic on HIV testing rates across four geographically diverse urban centres in the United States: An observational study - Ethan Moitra; Jun Tao; Joseph Olsen; Riley D. Shearer; Brian R. Wood; Andrew M. Busch; Andrea LaPlante; Jason V. Baker; Philip A. Chan (Elsevier, 2022)
Summary: Background: Non-emergent clinical services were limited or suspended during the early stages of the coronavirus disease 2019 (COVID-19) pandemic in the United States (U.S.). This could adversely impact epidemics of public health importance, such as HIV, and access to testing, which is a cornerstone of prevention efforts. Methods: In this observational study, we collected HIV testing and positivity rate clinical data from four geographically diverse U.S. healthcare systems in New Orleans, Louisiana; Minneapolis, Minnesota; Providence, Rhode Island; and, Seattle, Washington. Data from 2019 to 2020 were examined to assess changes in HIV testing in community-based, emergency department, and outpatient settings. Poisson regression was used to explore trends in HIV testing through phases of the COVID-19 pandemic. Findings: In outpatient settings, there was a 68-97% reduction in the number of HIV tests per week during each state's stay-at-home order period, compared to during the pre-stay-at-home order period in early 2020. HIV testing remained reduced 11-54% after states transitioned to advisory phases. The HIV positivity rate increased slightly at outpatient settings, except in New Orleans where it fell. Interpretation: We found a concerning trend of substantially decreased HIV testing across four geographically diverse sites. These findings suggest that new HIV infections within the U.S. may be undiagnosed and not yet linked to clinical care and services, as a consequence of the COVID-19 pandemic. Thus, augmented efforts to identify patients and link them to HIV services will be needed as healthcare settings return to full operation. Funding: U.S. National Institute of Mental Health.